Meningkatkan Kemampuan Motorik Halus Anak Usia Dini Melalui Kegiatan Menganyam Pada Kelompok B TK Negeri Pembina Bungoro - Lidia; Fitriani M; Siti Sahwin; Muhamad Yusril (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Abstract The development of fine motor skills in Group B children aged 5-6 years at Pembina Bungoro Kindergarten for the 2022/2023 school year shows that the fine motor development of children is still underdeveloped. It can be seen in the activities of cutting, coloring, writing and so on, there are still those who need the help of the teacher in completing assignments given by the teacher, for example when coloring children are still stiff in holding the coloring and coloring pictures given by the teacher, the development of children's fine motor skills is not yet well developed class action research methods using demonstration models, efforts to overcome the slow development of fine motor skills in early childhood group B at Pembina Bungoro State Kindergarten the researchers carried out weaving activities with origami paper. In cycle 1 the weaving activity uses origami paper and develops in each cycle where each cycle consists of two meetings, the child's fine motor development is not yet developed (BB) 6 children or 33.3%, starting to develop (MB) 7 children or 38.8 %, and developing as expected (BSH) 5 children or 27.7% in cycle I first meeting and increased in cycle I second meeting Then in cycle II children's fine motor skills increased as can be seen in the first meeting of cycle II at the first meeting of the child category undeveloped (BB) to 3 children or 16.6%, in the category starting to develop (MB) 4 children or 22.2%, then developing according to expectations (BSH) 6 children or 33.3%, and in the very well developed category (BSB) there are 5 children or 27.7%. And in cycle II the second meeting it can be seen that the children have made rapid progress where (BB) and (MB) are no longer there and in (BSH) there are 11 children or 61.1% and (BSB) 7 children or 38.9 %.